XMM-Newton Survey of the Magellanic Bridge - Le Roux, Ryan (Department of Astronomy, 2021)
We aim to characterise the X-ray binary population as a function of the local stellar population (in terms of age, metallicity, and stellar density) in the Magellanic Bridge, the interconnecting region between the Small and Large Magellanic Cloud. Gardiner and Noguchi (1996) suggest that closest approach between Small and Large Magellanic Cloud, as evidenced by dramatic phase shift in star formation, occurred approximately 200 Myr ago. During the approach, gas had been tidally stripped (most likely from the Small Magellanic Cloud) into the interconnecting Bridge. According to models of star formation history (Harris, 2007), alongside optical surveys of the Bridge (Skowron et al., 2014), there is strong evidence to suggest that the young, low metallicity stellar population formed in situ, rather than being tidally stripped from either Magellanic Cloud. Three fields located near the Western Bridge observed by Harris (2007) were also observed with the XMMNewton. Cross-matching between optical and X-ray sources was performed, and any interesting matches were followed up with spectroscopic analysis, using the 1.9 m telescope located in Sutherland. A Be/X-ray Binary (BeXRB) candidate is discussed, and if confirmed, will be the furthest known BeXRB from the SMC.